Dermatoglyphics: Processing Fingerprints for the Recognition of Innate Multiple Intelligences in an Individual - Oindri, Majumdar (My University, 2015)
From time immemorial, human beings have craved upon the idea of knowing the unknown. Quite surprising though, getting to know the future that has not even occurred, has been bestowed greater importance than what we all have already been born with. Fingerprints are the mirrors to our inborn talents and potentials, knacks and likings. If not recognised duly and well in time, they may remain shadowed all through a person’s life. What follows next is a life full of resentments and frustrations of underperformance at work or dissatisfaction of occupation. In this study, fingerprints of 18 individuals of Thapar University were acquired. Out of them, 12 subjects are recognized in the field of fine arts. The patterns were preprocessed for enhancement. The affine transformations were registered in the acquired images using Fourier Mellin transform, which registered 5 out of 6 similar dermal patterns. On the other hand, all the different patterns when correlated with each other, showed mismatch for perfect image registration. The Phase Only Correlation has shown a 85 percent pattern matching on 58 patterns. This algorithm was designed for a two class classifier of two dermal patterns, the loop and whorl. This study reveals that people having imitative and creative artistic intelligence have whorls and ulnar loops as the most occurring dermal patterns.
ME, EIED
Keywords: Dermatoglyphics; pattern matching; Phase only Correlation; Fourier Mellin Transform; Gabor Filter; Hough Transform; eied